Acceptance And Shelf Life Of The Raisins And Edamame Brew As a Healthful Drink For Elementary School Kids - Imelda Telisa; Annisa Mariyaulfa; Terati Terati; Arif Dwisetyo Haripamilu (Poltekkes Kemenkes Mataram, 2024)
Background: Brew drinks are one type of functional food. When elementary school-aged children show signs of malnutrition, they can have this drink—made from edamame beans and raisins—for breakfast or as a snack. Edamame beans, raisins, maltodextrin, tween 80, vanilla, and salt are the ingredients used to make this brewed drink. This study aims to optimize edamame bean and raisin drinks' nutritional value, shelf life, and formulation.Research Methods: This study used a completely randomized design with two factorials: the weight of edamame beans and raisins with four formulas. Thirty-five untrained panelists carried out sensory tests in the food laboratory of the Palembang Health Polytechnic Nutrition Department, and proximate tests were carried out in the CV Saraswati Bogor laboratory.Research Result: Formulation 1 (30 grams of edamame beans, 10 grams of raisins) is the chosen brewed drink formula based on the sensory data acquired. For every 100 grams of brewed drink, Formula 1 measured the energy content: 404.82 kcal, 8.6% protein, 5.58% fat, 79.96% carbohydrates, 4.21% water, and 1.5% ash. In the meantime, this brewed beverage has a two-month shelf life.Conclusion: The acceptance of edamame beans and raisins beverages varies depending on the mouthfeel and flavor. After a drink was steeped in edamame beans and raisins for 60 days, the Total Plate Count (TPC) test yielded a value of 0.